Recent Advances in Nonfullerene Acceptor‐Based Layer‐by‐Layer Organic Solar Cells Using a Solution Process. Issue 25 (6th July 2022) - Jee, Min Hun; Ryu, Hwa Sook; Lee, Dongmin; Lee, Wonho; Woo, Han Young
Abstract: Recently, sequential layer‐by‐layer (LbL) organic solar cells (OSCs) have attracted significant attention owing to their favorable p–i–n vertical phase separation, efficient charge transport/extraction, and potential for lab‐to‐fab large‐scale production, achieving high power conversion efficiencies (PCEs) of over 18%. This review first summarizes recent studies on various approaches to obtain ideal vertical D/A phase separation in nonfullerene acceptor (NFAs)‐based LbL OSCs by proper solvent selection, processing additives, protecting solvent treatment, ternary blends, etc. Additionally, the longer exciton diffusion length of NFAs compared with fullerene derivatives, which provides a new scope for further improvement in the performance of LbL OSCs, is been discussed. Large‐area device/module production by LbL techniques and device stability issues, including thermal and mechanical stability, are also reviewed. Finally, the current challenges and prospects for further progress toward their eventual commercialization are discussed. Abstract : Layer‐by‐layer (LbL) organic solar cells (OSCs) have attracted growing attention, showing photovoltaic performance comparable to their bulk heterojunction counterparts. Recent developments on nonfullerene acceptor‐based LbL OSCs are discussed by considering vertical p–i–n morphology control, exciton diffusion/separation, and large area device fabrication.